A NEW SPECIES OF BEGONIA (BEGONIACEAE) FROM SUMBAWA, LESSER SUNDA ISLANDS, INDONESIA - DEDEN GIRMANSYAH (BRIN Publishing (Penerbit BRIN), 2016)
GIRMANSYAH, D. 2016. A new species of Begonia (Begoniaceae) from Sumbawa, Lesser Sunda Islands, Indonesia. Reinwardtia 15(2): 115 – 118. — A new species of Begonia L. (Begoniaceae), Begonia semongkatensis Girm., is described from Sumbawa Island, Lesser Sunda Islands, Indonesia. The species belongs to Begonia section Reichenheimia. An illustration, identification key and distribution maps are provided.